2013
DOI: 10.3389/fpsyg.2013.00477
|View full text |Cite
|
Sign up to set email alerts
|

Driver of discontent or escape vehicle: the affective consequences of mindwandering

Abstract: An emerging body of evidence suggests that our penchant for entertaining thoughts that are unrelated to ongoing activities might be a detriment to our emotional wellbeing. In light of this evidence, researchers have posited that mindwandering is a cause rather than a manifestation of discontent. We review the evidence in support of this viewpoint. We then consider this evidence in a broader context—with regards to mindwandering's antecedents, respecting the observation that people frequently find pleasure in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 96 publications
(120 reference statements)
0
39
1
Order By: Relevance
“…Might mental health and thought content dynamically influence each other, creating positive feedback loops? While some studies have found initial evidence for causal relationships between the frequency and/or content of self-generated thoughts and wellbeing (Moberly and Watkins, 2008; Smallwood et al, 2009a; Killingsworth and Gilbert, 2010; Smallwood and O’Connor, 2011; Marchetti et al, 2012a; Ruby et al, 2013), a complete understanding of the nature of these relationships will require overcoming several methodological and conceptual challenges (Mason et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Might mental health and thought content dynamically influence each other, creating positive feedback loops? While some studies have found initial evidence for causal relationships between the frequency and/or content of self-generated thoughts and wellbeing (Moberly and Watkins, 2008; Smallwood et al, 2009a; Killingsworth and Gilbert, 2010; Smallwood and O’Connor, 2011; Marchetti et al, 2012a; Ruby et al, 2013), a complete understanding of the nature of these relationships will require overcoming several methodological and conceptual challenges (Mason et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…, p. 291). The frequent daydreaming of these individuals differs from typical self‐generated thought (which also occurs frequently) in that it is highly immersive as well as highly rewarding and enjoyable; negative feelings associated with this phenomenon have more to do with the social embarrassment or guilt associated with these excessive fantasies, as opposed to the content of the fantasies themselves …”
Section: Positively Biased Self‐generated Thoughtmentioning
confidence: 92%
“…To our knowledge, a single‐subject case study reported by Mason and colleagues has been the only investigation of the phenomenon of “excessive” daydreaming with functional neuroimaging. Researchers compared brain activation during this individual's fantasies to a condition where the subject was asked instead to concentrate intensively on a task, and found widespread activations associated with daydreaming (Fig.…”
Section: Positively Biased Self‐generated Thoughtmentioning
confidence: 99%
“…However, research increasingly acknowledges that daydreaming is unlikely to be a homogenous experience and has begun to explore the conditions under which daydreaming is associated with negative and positive emotion. For example, the relationship between daydreaming and emotion may depend on its phenomenological and emotional content (Andrews-Hanna et al, 2013;Poerio, Totterdell, & Miles, 2013), temporal focus (Ruby, Smallwood, Engen, & Singer, 2013), interest in thought content (Franklin et al, 2013), personal lay theories (Mason, Brown, Mar, & Smallwood, 2013) and current depressive symptomology (Marchetti, Koster, & De Raedt, 2012). As an extension to these factors we propose that the social content of daydreaming will also have an impact on how daydreaming relates to emotional well-being and, in particular, to positive social feelings rather than negative emotion more generally.…”
Section: Daydreaming and Emotionmentioning
confidence: 98%